Digital Education Innovation to Accelerate Stunting Reduction: An Experimental Study of Nutrition Class Mentoring Through SIGINTING - Adinda Putri Sari Dewi; Umi Laelatul Qomar; Ghufron Zaida Muflih (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Stunting is a priority problem in Indonesia because it inhibits child growth and development, reduces intelligence, increases the risk of disease, and negatively impacts productivity and the nation's economy. Therefore, stunting prevention is included in the government's Asta Cita program to improve the quality of human resources. However, there is still a gap in the use of technology and monitoring of child growth and development in mothers with stunted children, so that innovative interventions in the SIGINTING application are needed to strengthen the nutritional information system and increase the effectiveness of mentoring and follow-up of stunting cases. The purpose of this study was to improve mothers' knowledge, attitudes, and skills in reducing stunting through nutrition class mentoring with digital educational innovations through the Stunting Response Information System Application (SIGINTING). This type of research is a Quasi-experimental study with a pre-test-post-test control group design, with a sample size of 84 people in each group. The sampling technique used stratified random sampling. Data analysis used the Wilcoxon test. The results showed that the mean value of the level of knowledge before the intervention in the treatment group was 68.7 and after the intervention became 88.79 with a p-value of 0.000. Meanwhile, the mean value of mothers' attitudes before the intervention in the treatment group increased from 64.14 to 74.11 with a p-value of 0.000. The mean maternal skills score before the intervention was 70,64, increasing to 88,79 after the intervention, with a p-value of 0.000. The combination of nutrition class support and the use of the SIGINTING application has proven effective in improving maternal knowledge, attitudes, and skills in reducing stunting rates. Recommendations include implementing regular nutrition classes for mothers of toddlers and utilizing the SIGINTING application as a digital educational medium.